A study of possible reasons of the damage by electric current of traction induction motors bearings onboard of electric trains «Lastochka» - Pustovetov М.Yu.; Indylova N.V. (Научно-технический вестник Брянского государственного университета)
There is a problem of damage of bearings of traction induction motors of electric trains «Lastochka» by electric current. Based on the fact that the bearings have a ceramic insulation coating, and the cases of its electrical breakdown is not fixed, the authors put forward a version that a high-frequency current flows through the bearing as through an electric capacitance. The analysis show that the cause of the current can be a radio standard GSM-R The proposed technical solution against the damage of bearings: the use of grounding shaft rings and replace the bearings on the other with ceramic rolling elements.